Solving Unit Commitment Problem Using Mixed Integer Linear Programming for Demand Side Management - Ahmed Abubakar, Elwan; Mohd Hafiz, Habibuddin; Yanuar Zulardiansyah, Arief (Springer Nature Singapore Pte Ltd., 2024)
The implementation of demand side management (DSM) for an industrial plant by solving a unit commitment problem (UCP) is hoped to solve imbalances between electricity supply limitations and demand requirements which many times lead to a partial or total shutdown of production plants because of trips due to under voltage or high frequency when the supply is overloaded or a unit is suddenly stopped, while there is a need to maintain production. For this study, the cement industry was divided into operating units, simulated under two scenarios, and solved using mix integer linear programming (MILP) in an Excel solver. The result shows that there is a reduction in cost by 30% from $1203 to $880 for the same production requirement.